A Study on Treatment Guidelines of Lom Disease in Elderly According to Thai Traditional Medicine Textbooks - Namvises, Nittaya; Chansangsa, Siripuk; Hattapasu, Jiraporn; Nanta, Kannika (Journal of Graduate MCU KhonKaen Campus, 2023)
The purpose of this study was to investigate symptoms, causes, and treatment of Lom disease in Elderly that appeared In Thai Traditional Medicine (TTM) Textbooks. It is qualitative research by reviewing TTM textbooks and focus group discussion. Then, the data were analyzed for validation and settled as a guideline for teaching and learning in School of Traditional and Alternative Medicine (STAM), Chiang Rai Rajabhat University. The results found that there were 5 symptoms of Lom disease in elderly as follows; 1) feel feverish, 2) dizziness, 3) chest tightness, 4) flatulence, and 5) sweating abnormal. These symptoms were related with climate change, especially before raining. Moreover, treatment guidelines in TTM textbooks had 2 guidelines including; 1) pharmacological therapeutics by using herbal formula such as Yahom Nawakoth, Yahom Thepajit etc. for excessive wind elimination in the body, and 2) manus therapeutics for management of wind and blood circulation in Kalataree line by covering arms, legs, flanks, back, shoulder, neck-head and abdomen. These treatments could manage wind and blood circulation into normal state and prevented illness. In conclusion, the results showed that TTM textbooks were appeared the knowledge and treatment guidelines of Lom disease in elderly by pharmacological therapeutics and manus therapeutics. These data could be applied and used in teaching and learning about treatment disease for TTM students.